A dictionary of literary symbols - Ferber, Michael (Cambridge University Press, 2007)
This is the first dictionary of symbols to be based on literature, rather than universal psychological archetypes or myths. It explains and illustrates the literary symbols that we all frequently encounter, and gives hundreds of cross-references and quotations. The dictionary concentrates on English literature, but its entries range widely from the Bible and classical authors to the twentieth century, taking in American and European literatures.